Somatic mosaicism and variant frequency detected by next-generation sequencing in X-linked Alport syndrome - Fu, Xue Jun (Eur J Hum Genet, 2016)
X-linked Alport syndrome (XLAS) is a progressive, hereditary nephropathy. Although men with XLAS usually develop end-stage renal disease before 30 years of age, some men show a milder phenotype and develop end-stage renal disease later in life. However, the molecular mechanisms associated with this milder phenotype have not been fully identified. We genetically diagnosed 186 patients with suspected XLAS between January 2006 and August 2014. Genetic examination involved: (1) extraction and analysis of genomic DNA using PCR and direct sequencing using Sanger's method and (2) next-generation sequencing to detect variant allele frequencies. We identified somatic mosaic variants in the type VI collagen, α5 gene (COL4A5) in four patients. Interestingly, two of these four patients with variant frequencies in kidney biopsies or urinary sediment cells of ≥50% showed hematuria and moderate proteinuria, whereas the other two with variant frequencies of <50% were asymptomatic or only had hematuria. De novo variants can occur even in asymptomatic male cases of XLAS resulting in mosaicism, with important implications for genetic counseling. This is the first study to show a tendency between the variant allele frequency and disease severity in male XLAS patients with somatic mosaic variants in COL4A5. Although this is a very rare status of somatic mosaicism, further analysis is needed to show this correlation in a larger population.